414 Behaviors and Quality of Life in Children with Neurodevelopmental Disorders Undergoing Refractive Surgery. (April 2022) - Zdonczyk, Alexandra; Tychsen, Lawrence; Reynolds, Margaret
Abstract : OBJECTIVES/GOALS: The goal of this project is to characterize the adaptive and social behaviors of ametropic children with neurodevelopmental disorders (NDD) including Autism Spectrum Disorder (ASD) undergoing refractive surgery due to spectacle intolerance. Eye-related quality of life and visual behaviors will also be measured. METHODS/STUDY POPULATION: This is an ongoing prospective cohort study of children with NDD who are spectacle-intolerant and undergoing refractive surgery at St. Louis Childrens Hospital starting July 2020. The method of refractive surgery (photorefractive keratectomy (PRK), phakic intraocular lens implantation (phIOL), and refractive lens exchange (RLx)) is chosen based on degree and type of refractive error, astigmatism, and characteristics of the cornea and anterior chamber. Behaviors are characterized using the Adaptive Behavioral Assessment System, 3rd edition (ABAS-3) and Social Responsiveness Scale, 2nd edition (SRS-2), completed by parents/caregivers. Eye-related quality of life is measured using the pediatric Eye Questionnaire (PedEyeQ). Visual behaviors are assessed with optokinetic nystagmus tracking. RESULTS/ANTICIPATED RESULTS: In a preliminary sample of 9 patients, 4 have undergone PRK, 3 phIOL, and 2 are awaiting surgery. Pre-surgical SRS-2 scores had a median t-score of 70 (range 57 to 90), indicating a clinically significant deficiency in reciprocal social behaviors as this score is consistent with moderately severe ASD. Pre-surgical ABAS-3 scores had a median General Adaptive Composite (GAC) of 51 (range 48 to 74.5). This corresponds to a percentile of 0.100 (range <0.1 to 19th percentile for age). As rated by the Parental PedEyeQ, the domains most affected were "Parent Worry About Childs Eye Condition" (median 42.0, range 15.0 to 80.0) and "Parent Worry About Functional Vision" (median 18.8, range 3.2 to 68.7), where 0 represents the worst quality of life or functional vision and 100 the best. DISCUSSION/SIGNIFICANCE: Prior research has shown that refractive surgery can improve observed visual awareness, attentiveness, or social interactions in children with NDD. This is the first study to characterize the baseline adaptive/social behaviors and quality of life using validated surveys, with the goal of subsequently identifying patients most likely to benefit.